How many factors does the sense of community index assess?. Issue 3 (15th January 2018) - Loomis, Colleen; Wright, Carrie
Abstract: Studies of university students' sense of community (SOC) use various scales, one of which is the widely used Sense of Community Index (SCI), conceptualized as a 4‐factor model: membership, influence, needs fulfillment, and shared emotional connection. Research has been unable to show a reliable 4‐factor solution. One possible explanation may be that negatively worded items contribute to lack of model fit, which would be consistent with the claim that SOC was conceptualized as a unipolar positive construct. Data were collected using a positively worded SCI ( N  = 794). Four models were tested with confirmatory factor analysis in structural equation modeling: 1‐factor, theorized four‐factor, revised 3‐factor, and revised 4‐factor. None of the models showed good fit, though the fit of the 1‐factor model was improved over the 4‐factor. More studies are needed to attempt replication with a positively worded SCI.